Assimilação por bactérias do carbono e nitrogênio provenientes da matéria orgânica excretada e celular de Planktothrix agardhii - Tessarolli, Letícia Piton (2010)
The cyanobacterium Planktothrix agardhii is an important organism for the dynamics of Barra Bonita reservoir due to recurrent blooms throughout the year. However, there are still few published data on the dynamics of polysaccharides degradation and nitrogenous compounds excreted by the cells, as well as the way this process, and the compounds available, may affect the diversity and abundance of the bacterial community. This study aimed, therefore, to determine the feasibility of the released organic matter and cell biomass of cyanobacteria as the sole source of carbon and nitrogen for bacteria. Two similar experiments were performed: one using the dissolved organic matter (DOM) released by P. agardhii as a substrate for the establishment of a community from an inoculum from Barra Bonita reservoir and the second using cellular biomass of cyanobacteria as a substrate. Analysis of carbon and nitrogen, dissolved and particulate, provided the adjustment of a decay kinetic model, while counting and analysis of bacterial morphotypes, along with Denaturing Gradient Gel Electrophoresis (DGGE), were used to establish a possible process of bacterial succession by using these substrates. The settings in the kinetic model showed two phases of degradation for both nitrogen and organic carbon: first, a rapid phase, during the first three days of degradation, followed by a slower phase of degradation. The degradation coefficients of the first phase (kT) reached values up to 60x higher than those determined for the second phase of mineralization (k3). Our values for residual compounds are in agreement with published data on the reservoir, and may have ecological implications for the possibility of export to downstream areas. Bacterial concentrations in number and total biovolume of the samples provided a curve with a peak in the second and third days of experimental culture, followed by a decline, more pronounced in curves of biovolume due to the continuing reduction in the average value per bacterial cell found in cultures. The analysis of morphotypes showed no significant differences through time in cultures with DOM, however, in cultures with bacterial biomass, a reduction in the concentration of bacilli may be observed, with a consequent increase in the concentration of coccobacilli and cocci. A preliminary analysis of the DGGE showed changes in patterns of bands produced between days 1, 3 and 5 in both experiments, which may be indicative of a succession process in these cultures. The use of these sources of carbon and nitrogen by bacteria proved therefore feasible to maintain the bacterial community and a possible succession process has been suggested.